Synthesis and Characterization of Mixed Ligand Schiff Base Complexes of Aluminium with Isatin-3-Oxime - Gothwal, Y.K.; Joshi, Jyoti; S. Joshi, Bidya (Asian Journal of Chemistry, 2012)
The synthesis of some new mixed ligand complexes of aluminium containing Schiff bases and isatin-3-oxime (IO) derivatives have been reported. The complexes were prepared by the reaction of (Schiff base) aluminium isopropoxide with the isatin-3-oxime derivatives. The complexes were characterized by elemental analysis and spectral data. The studies reveal the formation of octahedral complexes.